Pengembangan Media Poster Pencegahan Obesitas pada Siswa di SMA Negeri 5 Surakarta - Kristina Eufrasia Seko (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Excessive fat accumulation is called obesity. Obesity occurs at all ages, but is most common in the first year of life, at school age and in adolescence. The main behavioral and risk factors for obesity include an unhealthy or unbalanced diet, lack of beneficial activities, such as smoking, and lack of fiber, such as vegetables and fruit. Therefore, preventing and controlling obesity is very important. Nutrition education is an educational approach that functions to increase teenagers' knowledge, attitudes and behavior towards nutritional problems. Education can be done using media, one of which is posters. Posters are a type of media that contain health information with a combination of clear visuals to attract readers' attention. Posters as a health promotion media have the advantage of increasing awareness, trust and attitudes towards health. The aim of this research is to develop poster media for obesity prevention for students at Senior High School 5 Surakarta. This research method uses Research and Development (R&D), with the ADDIE model being developed in 5 stages, namely (Analysis, Design, Development, Implementation, Evaluation). The results of this research showed that the assessment of poster media from stage 1 material experts was 59% inadequate, stage 2 material experts were 62% with decent results, and stage 3 material experts were 76% with decent results. Stage 1 media experts were 88% very decent results, and stage 2 and 3 media experts were 100% very decent. The media aspect got a percentage result of 91%, the media usefulness aspect was 89% which was very feasible. Overall, the average final assessment score was 89.9%, a very decent category. And a field trial was carried out which was attended by 30 students, producing results of 85% from the media aspect and 84% from the media usefulness aspect, including the very feasible category, so it can be concluded that the media developed is